The Ultimate Characters For Identity In Contemporary Architecture - Hashim Hameed El-Eqapy, Ahmed (Journal of Planner and Development, 2021)
General propositions have dealt with various indicators and features that frame and describe basic architectural concepts, and from those concepts, the concept of identity will be presented here, which represents the nerve of intellectual vision of the state of architecture development, transformation and change. Due to its deep intellectual basis, it was necessary to study multiple features, especially the achievement feature that was considered a major stage describing the nature of change and shift related to the achievement of concept and its role in the development of the architectural field .                                                                                            This research aims to clarify the general knowledge framework for the concept of identity and its general definitions in architecture and study its general features and transformations within levels and stages up to presenting its own vision between dynamic and achievement, and finally clarify its general achievement description to present the problem of research that specialized in weak knowledge clarification of general and detailed indicators of the achievement feature of identity in architecture, hence, the tendency to form a theoretical framework for the indicators related to that and graduation in their description, and after that to be applied to a specific and selected architectural product to represent the realization of the achievement nature of identity in architecture, so that the strength focus of the achievement feature for identity will be explored ascendingly from the generality of the features shifts to the achievement nature of the identity itself in the final conclusions and recommendations.